MENGAJAR YANG MEMBELAJARKAN - Mawardi Mawardi (Jurnal Ilmiah Didaktika, 2012)
The main problem faced by students in learning process is learning achievement. It is influenced by physiological, psychological, and environmental factor. Thus, educators play a major role in overcoming students’ learning problems through appropriate learning management. Learning is educator’s effort to teach students with a various learning strategies and sources, such as teachers, peers, environment, media, and others. Educators play an important role in facilitating the students to be actively learn to think, to speak, and to act in accordance with their teaching materials which being provided to achieve the expected competencies. The attendance of students in learning process is not only as passive participants in accepting the offered materials by the educators, but the student own broad freedom to develop their learning creativity to reach a maximum academic achievement in accordance with the capacity of each student’s competency.